The Queen [videorecording (DVD)] - Mirren, Helen; Cromwell, James; Sheen, Michael; McCrory, Helen; Jennings, Alex; Allam, Roger; Syms, Sylvia, 1934- (Miramax : Distributed by Buena Vista Home Entertainment, Inc. (1875), 2006)
An intimate, moving portrait of Queen Elizabeth and Tony Blair following the death of Diana. They struggle to reach a compromise between what was a private tragedy for the Royal Family and the public's demand for an open display of mourning.